As representações do crack de estudantes do ensino fundamental no município de Rio Grande-RS - Valério, Raquel Coelho (2011)
This scientific research aimed to investigate the representations of the crack of children and young elementary school students in Rio Grande, RS. The activities of field research was conducted in two stages, namely: I) The application of a questionnaire to a class of fifth grade at a public school, b) assembling a group of Workshops Theatre, composed of students different public schools, using audiovisual record of theatrical sketches created. Questionnaires and theatrical sketches, were analyzed in the Theory of Representations and the contributions of Henri Lefebvre. As the survey results and discussions on the representations found in relation to crack, it was possible objectivations, which indicate that the subjective process media are acting in instituting the hegemonic paradigm of the war on drugs, which anchors images in and around the crack, linking them with images of violence and social stereotypes. In that sense, this research found that users are represented by children and young people as drug addicts, while customers of drug pushers. However, without being criminalized, but represented either as individuals subject to social and medical intervention, sometimes liable to social degeneration and violence. And, as the main finding, the survey shows that the image of the money was perceived as being anchored near the core generator of representations, promoting ethical and moral conflicts in relation to the crack in everyday life, with the imagery and attitudes represented by the students